2016
DOI: 10.1097/iae.0000000000001033
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Hyperreflective Foci in Neovascular Age-Related Macular Degeneration Treated With Bevacizumab

Abstract: Quantity and location of HF are of prognostic value in intravitreal bevacizumab-treated naive neovascular age-related macular degeneration. Increased awareness of specialists interpreting optical coherence tomography scans toward the number and location of HF is prudent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…The authors assumed that due to more severe blood-retina barrier damage, eyes with HRF at baseline spectral domain OCT have more active CNV. Similar conclusions were also made by another study group [25] , which showed that resolution of HRF was associated with better final VA, while others found high amounts of HRF at baseline to indicate low VA [26] . So far, HRF have been hypothesised as a clinical marker of inflammatory response, aggregates of microglia-activated cells, protein and/or lipid deposits, and lipid-laden macrophages [15,20,21,25] .…”
Section: Discussionsupporting
confidence: 82%
“…The authors assumed that due to more severe blood-retina barrier damage, eyes with HRF at baseline spectral domain OCT have more active CNV. Similar conclusions were also made by another study group [25] , which showed that resolution of HRF was associated with better final VA, while others found high amounts of HRF at baseline to indicate low VA [26] . So far, HRF have been hypothesised as a clinical marker of inflammatory response, aggregates of microglia-activated cells, protein and/or lipid deposits, and lipid-laden macrophages [15,20,21,25] .…”
Section: Discussionsupporting
confidence: 82%
“…85 HRS have been recently evaluated in different retinal and choroidal conditions, such as early stages of DR, DME, AMD, and macular edema due to retinal vein occlusion. 63,65,[88][89][90][91][92][93][94][95][96][97] HRS with specific characteristics, such as dimension <30 lm, reflectivity similar to nerve fiber layer, absence of back-shadowing, and location in both inner and outer retina, were suggested to represent activated aggregates of microglial cells, thus can be considered an imaging biomarker of retinal inflammatory response (Fig. 2).…”
Section: Noninvasive Imaging Retinal Biomarkers Of Inflammation In Drmentioning
confidence: 99%
“…This feature of exudative disease also shows statistically significant reduction during anti-VEGF therapy. [51][52][53][54]…”
Section: Eyementioning
confidence: 99%
“…To date, only one study has reported resolution of hyperreflective foci to be associated with better visual outcomes. 70 Several investigators have found their resolution solely to be associated with reduction in central retinal thickness, 51,54 which per se has shown to lack correlation with visual function during the maintenance phase. Analyses of the impact of the mere presence and location of hyperreflective foci on visual function at baseline and during therapy have revealed that a high amount (420) of hyperreflective foci and a location in the inner and subretinal layers are associated with worse VA outcomes.…”
Section: Risk Of Progressionmentioning
confidence: 99%
See 1 more Smart Citation